2005
DOI: 10.1210/jc.2005-0212
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Levels in Adult Females: Changes with Age, Menopause, and Oophorectomy

Abstract: We report that serum androgen levels decline steeply in the early reproductive years and do not vary because a consequence of natural menopause and that the postmenopausal ovary appears to be an ongoing site of testosterone production. These significant variations in androgens with age must be taken into account when normal ranges are reported and in studies of the role of androgens in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
570
5
46

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 880 publications
(670 citation statements)
references
References 23 publications
49
570
5
46
Order By: Relevance
“…It has been reported that circulating androgens in postmenopausal women do not originate from the ovaries but from the adrenal gland since levels of androgens in postmenopausal women with natural menopause and those with surgical menopause were not different (89). It was later shown in a cross-sectional study that total and free testosterone levels in women aged 55 years or older with bilateral oophorectomy were significantly lower than those in age-matched women (90). A longitudinal study also showed a 42% decline in testosterone level in postmenopausal women who underwent oophorectomy, suggesting that the postmenopausal ovary is hormonally active and contributes significantly to the circulating pool of testosterone (91).…”
Section: Site Of Androgen Production In Postmenopausal Womenmentioning
confidence: 99%
“…It has been reported that circulating androgens in postmenopausal women do not originate from the ovaries but from the adrenal gland since levels of androgens in postmenopausal women with natural menopause and those with surgical menopause were not different (89). It was later shown in a cross-sectional study that total and free testosterone levels in women aged 55 years or older with bilateral oophorectomy were significantly lower than those in age-matched women (90). A longitudinal study also showed a 42% decline in testosterone level in postmenopausal women who underwent oophorectomy, suggesting that the postmenopausal ovary is hormonally active and contributes significantly to the circulating pool of testosterone (91).…”
Section: Site Of Androgen Production In Postmenopausal Womenmentioning
confidence: 99%
“…Serum estradiol levels were also lower in the same age group, but LH levels did not vary significantly in any of the age groups. Recent largescale cohort studies conducted in Australia [235][236][237][238], Norway [239], and United States [240] have provided further important insights into the overall pattern of ovarian sex steroids and gonadotropins that occur during the MT. It is reported that circulating FSH levels rise progressively during the MT and that in perimenopausal women estradiol production fluctuates with FSH and often reaches higher concentrations than those in young normal cycling women below the age of 35.…”
Section: Aging and Secretion Of Female Sex-steroidsmentioning
confidence: 99%
“…Numerous studies have reported that diurnal rhythmicity of cortisol [254,257,[269][270][271][272][273][274][275][276][277][278][279][280] and ACTH [238,263] is also unaffected by aging in both sexes, but there are some exceptions. For example, some studies reported higher evening [251,281] and morning [278] cortisol levels at older ages; higher 24h mean cortisol concentrations at older ages have also been reported in both men and women [269,270,272,281,282].…”
Section: Humansmentioning
confidence: 99%
“…Crosssectional studies have reported an age-related decrease in testosterone levels starting from the early reproductive years to the age of 65 years, followed by a small increase in late years. 25,26 However, recent insights from a longitudinal study suggest that circulating testosterone levels increase rather than decrease in women aged 38-50 years. 27 Testosterone exerts its biologic effects directly or through its metabolites (dihydrotestosterone (DHT) and estradiol).…”
Section: Testosterone Production and Actionmentioning
confidence: 99%